Silver-loaded HOFs material, preparation method and application
By using hydrogen bonded organic frames (HOFs) as carriers, nanosilver is stably embedded in the crystal structure, solving the problems of nanosilver instability and insufficient binding force of traditional carriers, achieving efficient and safe antibacterial effects and uniform distribution of silver ions.
Patent Information
- Application Number
- CN202510094073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-11
AI Technical Summary
Nanosilver is unstable in some media and is prone to agglomeration or precipitation, affecting its antibacterial effect and application effect. In addition, traditional carriers have problems of uneven loading and insufficient binding force, which increases the production complexity and risk of environmental pollution.
The hydrogen bonded organic framework (HOFs) composed of 1,3,5-phenyltriacetic acid (TMA), 4,4'-bipyridine (BPY) and BPY analogs were used as a new carrier, and nanosilver was stably embedded into the crystal structure through mechanical actions such as intermolecular hydrogen bonding and π-π stacking.
The stability and antibacterial activity of nano silver are improved, the inactivation problem caused by agglomeration is avoided, the uniform distribution and slow release of silver ions are achieved, the antibacterial time is extended, and the carrier has good biosafety.
Smart Images

Figure CN119792578A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silver-loaded HOFs material, a preparation method and application thereof, and belongs to the technical field of medical nanomaterials. Background Art
[0002] Silver nanoparticles (AgNPs) are nanomaterials with all sizes ranging from 1 to 100 nanometers. Due to their unique physical, chemical, and biological properties, silver nanoparticles have been widely used in many fields such as medicine, textiles, food packaging, cosmetics, environmental governance, electronics, sensors, and building materials. In the field of life sciences, silver nanoparticles have shown antimicrobial activity against various harmful pathogens and pathogenic microorganisms, including multidrug-resistant bacteria. First, among metal nanoparticles, silver is considered to be the most effective nanoparticle against bacteria and other microorganisms, and has a high degree of biocompatibility, which makes it easy to play a role in medical applications. Secondly, the antimicrobial activity of AgNPs has multiple mechanisms, indicating that they act on the cell membrane, affect intracellular components, and change the respiratory chain to achieve antibacterial effects. The latter is considered to be a major advantage because bacteria must simultaneously target multiple simultaneous mechanisms of action to develop resistance to AgNPs. It is for these reasons that AgNPs are also promoted as an alternative to antibiotics. However, AgNPs may be unstable in certain media and are prone to agglomeration or precipitation, which can affect their antimicrobial effects and application effects. Therefore, in antibacterial applications, AgNPs usually require stabilizers or carriers, or need to be functionalized or coupled with different molecules. However, the introduction of stabilizers and carriers may make the preparation process of nanosilver more complicated, increase production costs and time; in addition, if the stabilizer slows down the release rate of AgNPs, it may cause bacteria to come into contact with low concentrations of silver ions, increasing the risk of bacterial resistance. Some stabilizers may also be difficult to degrade in the environment, and long-term use may cause environmental pollution.
[0003] In order to solve the self-aggregation disadvantage of nanosilver, researchers introduced some carriers to load nanosilver. The main types of carriers are inorganic carriers and organic carriers. First of all, although inorganic carriers can enhance the dispersibility of nanosilver to a certain extent, there are still some problems. For example, during the drug loading process, nanosilver particles may not be evenly distributed on the surface or pores of the inorganic carrier, resulting in excessively high nanosilver concentrations in some areas and too low concentrations in some areas. This uneven loading will affect the antibacterial properties and stability of the material; and the binding force between nanosilver and inorganic carriers may be weak, causing nanosilver to fall off easily during use. This will not only reduce the antibacterial properties of the material, but may also cause potential harm to the environment and human body. In addition, due to the weak binding force, the stability of nanosilver on the carrier is poor, and it is easy to fall off or fail due to the influence of the external environment, thereby shortening the service life of the material. The organic carrier itself may have certain cytotoxicity and have adverse effects on organisms. Although the antibacterial properties of nanosilver are significant, excessive or long-term exposure to nanosilver may have a negative impact on human health; and the preparation process of organic carrier-loaded nanosilver is usually cumbersome, requiring precise control of reaction conditions and parameters. This increases the preparation cost and time, limiting its large-scale production and application. Summary of the invention
[0004] In order to solve these problems and develop more efficient and safe antibacterial agents, the present invention has developed a series of new carriers for loading AgNPs. These carriers not only solve the problem of nanosilver agglomeration, but also effectively enhance its antibacterial activity; at the same time, its biosafety is ensured. The carrier system is a binary eutectic system composed of 1,3,5-trimethylenediamine (TMA) and 4,4'-bipyridine (BPY) and analogs of BPY. It is called hydrogen-bonded organic framework (HOFs), which is a new type of porous crystalline material that assembles organic or metal-organic building blocks through intermolecular hydrogen bonding combined with π-π stacking, electrostatic interaction, van der Waals force and other intermolecular forces. As a drug delivery system, the advantage of HOFs lies in its high stability. The supramolecular interaction between drug molecules and carrier molecules enables the drug to be stably embedded in the crystal structure, thereby improving the chemical and physical stability of the drug; secondly, its advantage also lies in the controlled release performance. Due to the presence of HOFs, drug molecules can be released in a controllable manner within the crystal. This can achieve slow release of drugs, extend the shelf life of drugs, and reduce the frequency of medication. Third, it encapsulates the drug molecules and provides protection, preventing the drug from rapid degradation in the environment or in the body, which helps maintain the stability and activity of the drug.
[0005] A silver-loaded HOFs material includes a hydrogen-bonded organic framework compound and nanosilver loaded on the hydrogen-bonded organic framework; The hydrogen-bonded organic framework compound has a structure as shown in Formula I:
[0006] (I); Wherein, R refers to 4,4′-bipyridine or 1,4-bis(pyridin-4-yl)benzene or derivatives thereof with or without substitution, and the N in R is connected to the carboxyl group through a hydrogen bond.
[0007] R is 4,4′-bipyridine, 1,4-bis(pyridin-4-yl)benzene, 2,2′-dimethyl-4,4′-bipyridine or a derivative thereof.
[0008] The preparation method of the silver-loaded HOFs material comprises the following steps: Dissolve 1,3,5-benzenetricarboxylic acid in an alcohol solvent, drop the nanosilver suspension, take the upper layer solution after standing, add 4,4'-bipyridine or its derivatives, continue the reaction, wash the product and centrifuge it.
[0009] The weight ratio of 1,3,5-benzenetricarboxylic acid, 4,4′-bipyridine or its derivatives, and nanosilver is in the range of 1:0.5-1.5:0.05-0.15.
[0010] The alcohol solvent is methanol.
[0011] The reaction time is 1-20h.
[0012] The above silver-loaded HOFs materials are used in the preparation of in vitro or in vivo antibacterial materials.
[0013] The beneficial effects of the present invention are: Due to its excellent performance, it is used as a carrier of AgNPs to make it more stable and avoid the inactivation problem caused by self-aggregation, so that the antibacterial activity can be maintained for a longer time; the carrier can provide a suitable environment to prevent the instability of silver nanoparticles during storage, transportation or application. In addition, due to the difference in the concentration of silver nanoparticles inside and outside the system, the silver nanoparticles can be slowly and continuously released from the pores to the outside. Therefore, the binary eutectic material loaded with silver nanoparticles has the function of sustained release of silver nanoparticles, which can prolong the antibacterial time. Nanosilver loaded on HOFs can effectively control the dispersibility of nanometal particles and prevent nanosilver from self-aggregation, so that silver ions are more evenly distributed, thereby increasing its contact area with bacteria and enhancing the antibacterial effect. The carrier has good biosafety and can be applied in the field of life sciences. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 : XRD patterns of TMBP, TMDD, TMDM, TMBP-Ag, TMDD-Ag, and TMDM-Ag.
[0015] Figure 2 : Transmission electron microscopy images of TMBP-Ag, TMDD-Ag, and TMDM-Ag.
[0016] Figure 3 : Transmission electron microscopy image of AgNPs.
[0017] Figure 4 : Transmission electron microscopy image of AgNPs.
[0018] Figure 5 : TEM-EDS images of TMBP-Ag, TMDD-Ag, and TMDM-Ag and the corresponding energy dispersive X-ray spectroscopy elemental mappings of C, N, O, and Ag.
[0019] Figure 6 : Photos of Escherichia coli plates treated with different concentrations (0, 5, 10, 20, 40 μg / mL) of AgNP, TMDDAg, TMDMAg, and TMBPAg (left) and quantitative statistical graphs of bacterial mortality (right), n=3.
[0020] Figure 7 : Cytotoxicity evaluation of HOFs and HOF-Ag at different concentrations on HUVECs (left) and HaCaTs (right) for 48 hours, n=3.
[0021] Figure 8 : Skin wound images of mice in the control group, TMBP, AgNP, and TMBP-Ag groups on days 0, 4, 7, 11, and 14. Fig. 9 : Quantitative statistical graphs of wound healing rates of control group, TMBP, AgNP, and TMBP-Ag. (p<0.05), **(p<0.01), ***(p<0.001), and ****(p<0.0001). DETAILED DESCRIPTION
[0022] Raw materials: 1,3,5-benzenetricarboxylic acid (TMA), 4,4′-bipyridine (BPY), 1,4-bis(pyridin-4-yl)benzene (DDPB), 2,2′-dimethyl-4, 4′-bipyridine (TMDM), silver nanoparticles (AgNPs). Solvent: methanol.
[0023] Three types of hydrogen-bonded organic frameworks (HOFs-Ag) loaded with nanosilver were prepared.
[0024] The first is a eutectic encapsulated nanosilver system prepared by 1,3,5-benzenetricarboxylic acid (TMA) and 4,4′-bipyridine (BPY), referred to as TMBP-Ag; The second is a eutectic encapsulated nanosilver system prepared from 1,3,5-benzenetricarboxylic acid (TMA) and 1,4-bis(pyridin-4-yl)benzene (DDPB), referred to as TMDD-Ag; The third type is a eutectic-encapsulated nanosilver system prepared by 1,3,5-benzenetricarboxylic acid (TMA) and 2,2′-dimethyl-4, 4′-bipyridine (DMPD), referred to as TMDM-Ag.
[0025] All syntheses were carried out in methanol.
[0026] The main steps are: 1,3,5-benzenetricarboxylic acid is evenly dispersed in methanol, nanosilver suspension is added as the target drug, and then basic ligands (4,4′-bipyridine or 1,4-bis(pyridin-4-yl)benzene or 2,2′-dimethyl-4,4′-bipyridine) dissolved in methanol are added. The acid-base ligands are self-assembled to wrap the nanosilver, thereby preparing HOFs-Ag.
[0027] The synthesis steps of the above three HOFs-Ag are as follows: 1) Preparation of 1,3,5-benzenetricarboxylic acid (TMA) and 4,4′-bipyridine (BPY) cocrystal (TMBP-Ag) loaded with AgNPs: Dissolve 100 mg TMA in 10 mL methanol, dissolve in a 90°C water bath by ultrasonication, slowly add reduced nanosilver suspension (10 mg, 5 mL) while stirring, let stand for 10 minutes, take the upper layer solution, and then add 10 mL of BPY (100 mg) dissolved in methanol. Stir at 1000 rpm for 6 h. Centrifuge at 3000 rpm for 5 min. Wash with methanol 3 times. Store in methanol after centrifugation.
[0028] The synthetic route is as follows:
[0029] 2) Preparation of 1,3,5-benzenetricarboxylic acid (TMA) and 1,4-bis(pyridin-4-yl)benzene (DDPB) cocrystals (TMDD-Ag) loaded with AgNPs: 100 mg TMA was dissolved in 10 mL methanol, dissolved by ultrasonication in a 90°C water bath, and then the reduced nanosilver suspension (10 mg, 5 mL) was slowly added dropwise during stirring. After standing for 10 minutes, the upper layer solution was taken, and then 10 mL of DDPB (100 mg) dissolved in methanol was added. Stir at 1000 rpm for 6 h. Centrifuge at 3000 rpm for 5 min. Wash with methanol 3 times. After centrifugation, store in methanol.
[0030] The synthetic route is as follows:
[0031] 3) Preparation of 1,3,5-benzenetricarboxylic acid (TMA) and 2,2′-dimethyl-4, 4′-bipyridine (DMPD) cocrystal (TMDM-Ag) loaded with AgNPs: Dissolve 100 mg TMA in 10 mL methanol, dissolve in a 90°C water bath by ultrasonication, slowly add reduced nanosilver suspension (10 mg, 5 mL) while stirring, let stand for 10 minutes, take the upper layer solution, and then add 10 mL of DMPD (100 mg) dissolved in methanol. Stir at 1000 rpm for 6 h. Centrifuge at 3000 rpm for 5 min. Wash with methanol 3 times. Store in methanol after centrifugation.
[0032] The synthetic route is as follows:
[0033] Structural Verification Powder X-ray Diffraction: After HOFs-Ag was dried into powder, the crystals were verified by X-ray multi-crystal diffractometer.
[0034] Results: It was shown that there were specific crystal structures in the three materials, and characteristic peaks of nanosilver also appeared in the silver-loaded HOFs ( Figure 1 ).
[0035] Single crystal X-ray diffraction: A small piece of crystal of appropriate size is peeled off from the single crystal and the crystal structure is analyzed by single crystal X-ray diffraction.
[0036] Results: The characteristic peaks of the powder XRD pattern were consistent with the theoretical XRD pattern calculated by the peak shape function in single crystal X-ray diffraction, proving that the synthesized product has a certain crystal structure (2).
[0037] Transmission Electron Microscopy: HOFs-Ag was placed on a copper grid, and after the solvent evaporated, the morphology and distribution of nanosilver in the crystal were observed by electron microscopy. Results: The nanosilver particles had a high density on the surface of the three eutectics and were evenly distributed in the crystal at the same time, while the individual nanosilver particles were in an aggregated state. Figure 3 , Figure 4 ) Energy dispersive X-ray spectroscopy: HOFs-Ag was placed on a copper grid, and after the solvent evaporated, the distribution of elements in it was observed by energy dispersive X-ray spectroscopy. Results: C, N, O and Ag were evenly distributed throughout the crystal ( Figure 5 ).
[0038] 2. Evaluation of antibacterial properties A 96-well polystyrene ELISA plate was used, and Escherichia coli (Gram-negative bacteria) was used as the experimental strain. The minimum bactericidal concentration (MBC) was determined by the microbroth dilution method and the colony plate count method. Different concentrations (0, 5, 10, 20, 40 µg / mL) of antibacterial materials (100 μL each of TMBP-Ag, TMDD-Ag, TMDM-Ag, and AgNPs) were serially diluted in LB medium and added to the 96-well ELISA plate. The bacterial solution (10 6 CFU / mL, 100 μL), incubate in a shaker at 250 rpm and 37°C for 24 h, take 10 μL of the liquid in the 96-well ELISA plate, dilute it 10,000 times with sterile water, and then take 10 μL to spread on the agar plate, incubate in a 37°C incubator for 12 h, record the corresponding concentration of the plate without colony growth, repeat the experiment 3 times, and take the average value of the results obtained from the 3 experiments as the MBC value.
[0039] Results: In the in vitro antibacterial study, TMBP-Ag, TMDD-Ag, TMDM-Ag and AgNPs showed dose-dependent antibacterial activity ( Figure 6 Compared with AgNPs, the survival rate of E. coli induced by TMBP-Ag, TMDD-Ag, TMDM-Ag, and especially TMBP-Ag was much lower after co-incubation with bacterial suspension ( Figure 6 ).
[0040] 3. Biosafety Assessment CCK8 detection of cell viability: First, the Huvec cells or HaCaT cells with better growth conditions were digested and counted. 200 μL of culture medium containing 5000 cells was added to each well of a 96-well plate and cultured for 12 h at 37°C and 5% atmospheric CO2. A total of 6 groups were administered, namely TMBP, TMBP-Ag, TMDD, TMDD-Ag, TMDM, and TMDM-Ag. The control group was added with an equal volume of PBS and a suitable concentration gradient was set. Incubate for 48 h after administration. After 48 h of culture, observe the cell morphology and growth under a microscope. First, prepare CCK8 working solution according to the instructions (CCK8 stock solution: culture medium = 1:9), discard the drug-containing culture medium, add 150 μL PBS along the well wall to wash 3 times, then add 100 μL CCK8 working solution to each well, incubate in the dark for 30 minutes, use a multifunctional microplate reader to detect the absorbance at 450 nm, and substitute the following formula to calculate the cell survival rate: Cell survival rate = (absorbance value of experimental well - absorbance value of blank well) / (absorbance value of control well - absorbance value of blank well) × 100%.
[0041] Results: At a concentration of 50 μg / mL, after treatment with HUVECs and HaCaT for 48 hours, all groups showed higher cell viability (over 99.9%). In addition, we found that when the material concentration was 200 μg / mL, the HaCaT cell viability in the TMBP, TMDD, and TMDM groups could still reach 78.8%, 66.0%, and 60.5%, respectively ( Figure 7 ). This proves that the binary eutectic system has good biocompatibility.
[0042] 4. Effect of promoting wound healing in mice Twenty male C57 mice weighing 20-30 g were selected, shaved with an animal razor and depilatory cream, washed with water, wiped once with iodine and twice with 75% ethanol. A circular wound with a diameter of 7 mm was constructed on the left and right sides of the back. 10 μL of Staphylococcus aureus (10 6 CFU / mL). After 2 h of infection, the mice were randomly divided into 4 groups (n=5) and treated with saline, TMBP, TMBP-Ag (20 μg / mL), and AgNPs (20 μg / mL), respectively. Then, all treated wounds were covered with 3M film. The wounds were photographed and medicated on days 0, 4, 7, 11, and 14. After the experiment, the wound healing rate of each group was calculated as follows: Wound healing rate = (M0-Mn) / M0×100% Among them, M0 and Mn (n = 4, 7, 11, 14) represent the wound healing status on days 0, 4, 7, 11, and 14, respectively.
[0043] Results: Compared with saline, TMBP and AgNPs treatments, TMBP-Ag treatment significantly promoted wound healing and anti-inflammatory abilities ( Figure 8 , Fig. 9 ). The figure shows the comparison of wound areas analyzed by Image J software. It can be seen that the wounds in the saline, TMBP, and AgNPs groups healed very slowly until day 4, when the wound healing rates were 19%, 23.6%, and 26.9%, respectively. The TMBP-Ag group had a significant wound healing effect on day 4 (40.3%). In addition, the results of the wound healing experiment clearly showed that the wound closure rate in the TMBP-Ag group reached 96.6% after 14 days, which was much higher than that in the saline TMBP group and the AgNPs group (89.6%, 91.1%, and 90.9%, respectively).
Claims
1. A silver-loaded HOFs material, characterized in that: It includes a hydrogen-bonded organic framework compound and nanosilver loaded on the hydrogen-bonded organic framework; The hydrogen-bonded organic framework compound has a structure as shown in Formula I: (I); Wherein, R refers to 4,4′-bipyridine or 1,4-bis(pyridin-4-yl)benzene or derivatives thereof with or without substitution, and the N in R is connected to the carboxyl group through a hydrogen bond.
2. The silver-loaded HOFs material according to claim 1, characterized in that: R is 4,4′-bipyridine, 1,4-bis(pyridin-4-yl)benzene, 2,2′-dimethyl-4,4′-bipyridine or a derivative thereof.
3. The method for preparing the silver-loaded HOFs material according to claim 1, characterized in that: The steps include: Dissolve 1,3,5-benzenetricarboxylic acid in an alcohol solvent, drop the nanosilver suspension, take the upper layer solution after standing, add 4,4'-bipyridine or its derivatives, continue the reaction, wash the product and centrifuge it.
4. The method for preparing the silver-loaded HOFs material according to claim 3, characterized in that: The weight ratio of 1,3,5-benzenetricarboxylic acid, 4,4′-bipyridine or its derivatives, and nanosilver is in the range of 1:0.5-1.5:0.05-0.
15.
5. The method for preparing the silver-loaded HOFs material according to claim 3, characterized in that: The alcohol solvent is methanol.
6. The method for preparing the silver-loaded HOFs material according to claim 3, characterized in that: The reaction time is 1-20h.
7. Use of the silver-loaded HOFs material according to claim 1 in preparing in vitro or in vivo antibacterial materials.